Pengaruh Ekstrak Alga Cokelat (Sargassum sp.) terhadap Pertumbuhan Bakteri Escherichia coli Secara In Vitro [Effect of Brown Algae Extract (Sargassum sp.) on Growth of Escherichia coli In Vitro] - Moch. Amin Alamsjah; Dwi Nurhayati; Wahju Tjahjaningsih (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Algae Sargassum sp. showed the ability to inhibit the growth of a maximum of several types of pathogenic bacteria such as Escherichia coli. Because of Sargassum sp. have antibacterial with 2 active ingredients are compounds of phenol and tannin fiber. So Sargassum sp. potential to serve as antibakteri substances against several types of bacterial pathogens such as bacteria that cause diarhea.The aim of the study was to determine antibacterial activity brown algae exstract (Sargassum sp.) and determine best concentration from brown algae exstract (Sargassum sp.) to kill of E. coli. This study was conducted at several places such as Saints and Technology Faculty and Veterinary Faculty, Airlangga University Surabaya. Research was done September 2010. This study was conducted in the laboratory using experimental method completely randomized design with twelve treatments and there replications. The main objectives of this study were MBC extract of Sargassum sp. Result of the study analyzed with Khi-Khuadrat. Result of the study showed that extract Sargassum sp. has antimicrobial activity against E. coli were determined with in vitro method. Based on MBC data were found to be effective to kill of E. coli at 50 %. Exploration potential of extracts from brown algae (Sargassum sp.) against various species of bacteria that cause diarrhea are expected to become a new information about the content of extracts of Sargassum sp. as an antibacterial. Also from this research will be obtained an alternative treatment of diarrheal diseases that come from living marine resources and will eventually increase the economic value of fishery commodities which have not explored its use as Sargassum sp.